1993
DOI: 10.1104/pp.102.1.145
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand-Transfer Activity in Pea (Pisum sativum L.) Chloroplasts

Abstract: The occurrence of DNA recombination in plastids of higher plants is well documented. However, little is known at the enzymic level. To begin dissecting the biochemical mechanism(s) involved we focused on a key step: strand transfer between homologous parenta1 DNAs. We detected a RecA-like strand transfer activity in stromal extracts from pea (Pisum sativum 1.) chloroplasts. Formation of joint molecules requires MgZ+, ATP, and homologous substrates. This activity is inhibited by excess single-stranded DNA (ssDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…A number of recent reports indicate that a recA homolog functions in this way in plant chloroplasts (33)(34)(35)(36). To test this hypothesis, we preincubated mammalian mitochondrial extracts with control antisera, or immunoglobulin that had been affinity purified from recA antisera, using an Arabidopsis thaliana chloroplast recA homolog column (affinity purified antisera was kindly provided to us by Dr. A. Jagendorf, Cornell University).…”
Section: Mitochondrial Extract Hr Activity Is Not the Results Of Nuclementioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent reports indicate that a recA homolog functions in this way in plant chloroplasts (33)(34)(35)(36). To test this hypothesis, we preincubated mammalian mitochondrial extracts with control antisera, or immunoglobulin that had been affinity purified from recA antisera, using an Arabidopsis thaliana chloroplast recA homolog column (affinity purified antisera was kindly provided to us by Dr. A. Jagendorf, Cornell University).…”
Section: Mitochondrial Extract Hr Activity Is Not the Results Of Nuclementioning
confidence: 99%
“…Second, a number of nuclear-encoded yeast genes have been shown to be involved in mitochondrial recombination and repair (31,32). Finally, studies of DNA repair in plant chloroplasts have shown that a homolog of the bacterial recA gene is involved in DNA repair in that organelle (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…In addition, a plant Arabidopsis thaliana gene encoding a RecA homologue, which is distinct from Rad51/Dmc1 and closely related to bacterial RecA proteins, has been characterized and found to be targeted to chloroplasts (At1g79050 [AtcprecA]; Cerutti et al, 1992, Cao et al, 1997. RecA-like strand transfer activity was also detected in a stromal extract from pea chloroplast (Cerutti and Jagendorf, 1993). The complete nuclear genome sequence of A. thaliana (The Arabidopsis Genome Initiative, 2000) revealed the presence of two other recA genes (At3g10140 [AtmtrecA] and At2g19490) related to bacterial recA, and At3g10140 was reported to be targeted to mitochondria (Khazi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The higher plant Arabidopsis thaliana features Rad51 and Dmc1, eukaryotic counterparts for nuclear DNA recombination/repair (Bishop et al, 1992;Shinohara et al, 1992), and several bacterial-type RecA homologs encoded in the nucleus, which have been shown to be targeted to chloroplasts (Cerutti et al, 1992;Cao et al, 1997) and/or mitochondria (Khazi et al, 2003;Shedge et al, 2007). RecA-like strand transfer activity has been detected in a stromal extract from pea (Pisum sativum) chloroplasts (Cerutti and Jagendorf, 1993) and in soybean (Glycine max) mitochondria (Manchekar et al, 2006). In the moss Physcomitrella patens, two RecA homologs were identified, a mitochondrial-targeted RecA (RECA1) and a chloroplasttargeted RecA (RECA2) Inouye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%